Limiting Social Assistance under the EU Temporary Protection Directive to Displaced Persons Working Remotely for the Public Administration of Their Country of Origin - Sadowski, Piotr (Review of European and Comparative Law, 2024)
This research focuses on the legal situation of displaced persons who benefit from Directive 2001/55/EC regulating the EU temporary protection mechanism. This law can be activated in the case of mass influx of persons in need of international protection. A displaced person (unlike a refugee) can work remotely for the authorities of their country of origin, although this should be verified individually. Thanks to this, the financial benefits from this type of work can be taken into account by the country of residence of the displaced person when determining the level of social assistance granted to that person under Directive 2001/55/EC.